Perancangan Alih Fungsi Kontainer menjadi Modul Ruang Komersial “Barbershop” - Ricky Dwi Putra; Yusita Kusumarini; Meirina Kuncahyowati (Intra, 2019)
Surabaya is a city with a port, which has been considered to be the export import center in East Java. This causes a buildup of container because the cost for manufacturing a new container is cheaper than shipping back to their home countries. One way to overcome this problem is by refunctioning container into a space. Yayasan Pondok Kasih is a foundation that is engaged in the social sector, and one of the ideas that being planned by this foundation is to design several commercial spaces for its communities with the use of refunction containers as the media. One of the commercial space they want to create for their communities is barbershop. The design method used in this project is Design Thinking, and the concept for the modules is “one stop”. The use of this concept is to overcome the problem of circulation in a limited space, so multifunctional furniture is applied and efficient furniture arrangement regarding to the limited size of the container space. In addition from responding the cases from Yayasan Pondok Kasih, a new business idea can also be created by designing several types of barbershop commercial modules so that the module can be offered to the buyers who want to open a business with buildings from containers.